2014
DOI: 10.4100/jhse.2014.91.07
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plyometric training on sand versus grass on muscle soreness and selected sport-specific performance variables in hockey players

Abstract: Amrinder, S., Sakshi, G., & Singh, S.J. (2014). Effect of plyometric training on sand versus grass on muscle soreness and selected sport-specific performance variables in hockey players. J. Hum. Sport Exerc., 9(1), pp.59-67.The purpose of this study was to compare the effects of a 4-week plyometric training on two different surfaces, sand and grass on muscle soreness and selected sport-specific performance variables in national level hockey players. Subjects were randomly divided into two groups-grass training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…It has been reported that plyometric exercises play a significant role in improving balance ability [5,6]. However, most of previous studies were focused the long-term effects, thereby the short-term effects or immediate effects following plyometric intervention was uncertain until the present [7].…”
Section: Original Articlementioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that plyometric exercises play a significant role in improving balance ability [5,6]. However, most of previous studies were focused the long-term effects, thereby the short-term effects or immediate effects following plyometric intervention was uncertain until the present [7].…”
Section: Original Articlementioning
confidence: 99%
“…Among those interventions, plyometric exercises have been commonly used for athletes to improve their balance, which is important for making good results on the field [4,5]. Also, performing exercises on different surfaces is a common method used to improve balance [6].…”
Section: Original Articlementioning
confidence: 99%
See 2 more Smart Citations
“…Plyometric training is based on a collection of mechanical and physiological capabilities of the muscle [1]. This kind of training is applied in several stages of preparation (prior A to and during the season) in most athletic fields, attracting athletes' attention over the past decade [2].…”
Section: Introductionmentioning
confidence: 99%